Innovative solutions for masonry structures : conception, testing and application - Lourenço, Paulo B. (2008)
The evolution of structural masonry is briefly reviewed, from old thrust line behavior to modern global behavior using shear walls. For modern structural masonry, the use of unreinforced, confined and reinforced masonry is addressed, discussing the influence of seismic hazard and presenting different solutions adopted in developed countries. Finally, two building systems for modern masonry structures recently developed at University of Minho are presented, one based on lightweight concrete blocks and another based on normal concrete blocks. The experimental and numerical work carried out is addressed, together with conclusions on the performance of the system for in-plane lateral loading.